HBR'S 10 must reads: The definitive management ideas of the year from Harvard Business Review 2018. - Harvard Business School (Harvard Business Review Press, 2018)
HBR's 10 must be read series is the definitive sollection of ideas and best practices for aspiring and experienced leaders alike. These books offer essential reading selected from the pages of Harvard Business Review on topics critical to the success of every manager. The problem is product innovatios often flame out launch, sespite tremendous efforts to make them attractive, relevant, and up-to-date. Why it happens, customers don't wnt to spend the mental energy needed to choose between products. The solution to strenthen customer's hatbits, innovations should represent a progression of the brand rather than a break wiht the past.